Root Search Applications in Electric Vehicle Cooling Systems - Lisa, Ade; Anika (Etunas Sukses Sistem, 2023)
Electric vehicle cooling systems are crucial components that maintain the performance and life of batteries and electric motors through temperature regulation. This research aims to develop a mathematical root search-based application used in the optimization of electric vehicle cooling systems. The methodology used involves mathematical modeling of thermal and fluid flows in a cooling system, followed by the implementation of numerical methods, such as Newton-Raphson and Bisection, to solve non-linear equations related to cooling efficiency. The results show that this application is able to identify optimal operating parameters, such as fluid flow velocity and heat distribution, with high accuracy and efficient computing time. The conclusion of this study confirms that mathematical root search can be applied effectively in the design and operation of electric vehicle cooling systems. The contribution of this research to science includes the development of a systematic approach based on numerical algorithms that can be integrated in thermal simulation software for electric vehicles, thereby supporting innovation in the field of environmentally friendly transportation.